What happened to Anna K. : a novel - Reyn, Irina (New York : Simon & Schuster, 2008)
Married unhappily to a prominent member of her tight-knit Russian immigrant community, vivacious Anna K. engages in a reckless affair with an outsider on whom she has pinned fleeting hopes for freedom.
"A Touchstone book."
Keywords: Jews, Russian -- New York (State) -- New York -- Fiction; Married women -- Fiction; Families -- Fiction; Adultery -- Fiction; Agitation (Psychology) -- Fiction; Communities -- Religious aspects -- Fiction; Queens (New York, N.Y.) -- Fiction